1990
DOI: 10.1055/s-2007-1004983
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Hypertension

Abstract: Diabetes mellitus and hypertension constitute two powerful independent risk factors for cardiovascular, renal and atherosclerotic disease. The frequent occurrence of the two diseases in the same individual doubles the risk of cardiovascular death, as well as substantially increasing the frequency of transient ischemic attacks, strokes, peripheral vascular disease with lower extremity amputations, as well as end-stage renal disease and blindness. Although hypertension usually occurs in IDDM in association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Again, diabetes and hypertension are two associated non-communicable diseases. This was reported in separate studies [35][36][37][38][39].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Again, diabetes and hypertension are two associated non-communicable diseases. This was reported in separate studies [35][36][37][38][39].…”
Section: Introductionsupporting
confidence: 61%
“…Overweight, obesity, diabetes, hypertension is interrelated non-communicable diseases and are responsible for other non-communicable diseases [11,17,19,20,42,48,[50][51][52][53][54][55]. Diabetes and its related non-communicable diseases were well documented in home and abroad [35][36][37][38]55,56]. Suffering from diabetes for longer duration creates many types of complications in health, especially physical disability.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of cardiovascular disease (CVD)-related death is 2-3 fold greater in patients with both hypertension and diabetes than subjects with either isolated hypertension (at all levels of elevated systolic blood pressure) or diabetes (Fuller et al, 1983;Stamler et al, 1993). All of the CVD subclasses, which includes coronary heart disease (CHD) (angina, CAD, MI, CHF, sudden death), cerebrovascular disease (stroke) and peripheral vascular disease, contribute to the increase risk of CVD morbidity and mortality in diabetic hypertensive patients (Christlieb, 1982;Assmann and Schulte, 1988;Mahler, 1990;HDSG 3 , 1993;Hoy et al, 1995;Rossing et al, 1996). Microvascular complications such as end-stage renal disease and retinopathy are also accelerated and more frequently observed when diabetic patients are hypertensive (Knowler et al, 1980;Krolewski et al, 1988).…”
Section: A Clinical Presentation Of Hypertension In Diabetic Patientsmentioning
confidence: 99%
“…Hyperinsulinsm and insulin resistance may lead to hypertension through altered intracellular calcium metabolism, which will enhance renal sodium reabsorption or through an effect of insulin upon lipid and catecholamine metabolism [38]. Like the other study, the study does not simply consider the cases of diabetes and hypertension reported by the respondents.…”
Section: Discussionmentioning
confidence: 99%